2018
DOI: 10.1093/jat/bky091
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Exposure to Pyrimethanil After Controlled Human Experiments

Abstract: Pyrimethanil (PYM) is a fungicide used pre- and post-harvest on many crops. It has a low acute toxicity but is of toxicological concern because of its antiandrogenic properties. The aim of the current work was to investigate some metabolism and estimate elimination kinetics of PYM in humans after experimental oral and dermal exposure. A liquid chromatography triple quadrupole mass spectrometry (LC–MS-MS) method was developed and validated for the analysis of PYM and its metabolite 4-hydroxypyrimethanil (OH–PYM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…The chemicals included in this study are common among environmental, consumer, and occupational exposures. Pyrimethanil is a fungicide used in conventional fruit agriculture, and both workers and consumers can be exposed (Faniband et al 2019). Pyrimethanil has been found to be an aryl hydrocarbon receptor agonist in vitro (Medjakovic et al 2014) and has been shown to disrupt liver metabolism and thyroid hormones in rodents at high concentrations, 13-1,000 mg=kg=d (Hurley 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemicals included in this study are common among environmental, consumer, and occupational exposures. Pyrimethanil is a fungicide used in conventional fruit agriculture, and both workers and consumers can be exposed (Faniband et al 2019). Pyrimethanil has been found to be an aryl hydrocarbon receptor agonist in vitro (Medjakovic et al 2014) and has been shown to disrupt liver metabolism and thyroid hormones in rodents at high concentrations, 13-1,000 mg=kg=d (Hurley 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, pyrimethanil is mainly metabolized by oxidation to OH-pyrimethanil, after which conjugation (mainly with sulfonate) occurs. After oral exposure, 80% of the compound was found in urine as OH-pyrimethanil (Faniband et al 2019). Pyrimethanil is not considered of toxicological concern to humans below the ADI of 0:17 mg=kg=d and has low acute toxicity (https://efsa.onlinelibrary.wiley.com/doi/pdf/10.2903/ j.efsa.2006.61r).…”
Section: Discussionmentioning
confidence: 99%
“…The analyses were performed using a liquid chromatography system (UFLC RX ; Shimadzu Corporation, Kyoto, Japan) coupled with triple quadrupole linear ion trap mass spectrometer equipped with TurboIonSpray source (QTRAP 5500 and 6500+; AB Sciex, Foster City, CA, USA). The analyzed exposure biomarkers of the parent pesticides were 3-phenoxybenzoic acid A modified method based on Faniband et al [38] was applied for the simultaneous analysis of 3-PBA, 4F-3-PBA, CFCA, DCCA, TCPy, OH-PYM, OH-TBZ, OH-TEB, 2,4-D, and MCPA. In short, urine samples were enzymatically treated overnight with β-glucuronidase/arylsulfatase and extracted on 96-well solid phase extraction (SPE) plates before LC-MS/MS analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The measured concentrations only reflect exposure within the past 24 h and are probably associated with very recent intake of food, since these compounds have short biological half-lives [ 38 , 48 ]. Furthermore, the absolute measured urinary concentrations of each compound can be difficult to compare because the metabolism and toxicokinetic parameters of the compounds vary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation